The narrative reader - McQuillan, Martin (Routledge, 2000)
The Narrative Reader provides a comprehensive survey of theories of narrative from Plato to Post-Structuralism. The selection of texts is bold and broad, demonstrating the extent to which narrative permeates the entire field of literature and culture. It shows the ways in which narrative crosses disciplines, continents and theoretical perspectives and is a long overdue and welcome addition to the field. Canonical texts are combined with texts which are difficult to get hold of elsewhere, and new translations and introductory material are presented. The texts cover many crucial issues and topic.